Quality Chemicals, Microbiology and Antiodants of Ongole Beef Culled Se’i Using Lime Orange Juice, Kaffir Lime and Lemon Juice - Gemini E. M. Malelak; Yumita Elyk; Yakob R. Noach; Hendrikus Umbu Padu (Journal of Tropical Animal Science and Technology, 2023)
This study aims to determine the effect of the use of lime juice, kaffir lime juice and lemon on the chemical, microbiological and antioxidant qualities of se’i. The design used was Completely Randomized Design (CRD) with 4 treatments and replications.The treatment consisted of TJ = without citrus juice, JN = used of 3% lime juice, JP used of 3% kaffir lime juice/juice, JL used of 3% lemon juice. The variables studied included water content, protein content, fat content, total bacteria and Antioxidant. The results of statistical analysis showed that treatment had no significant effect (P>0.05) on water content, protein, fat, and antioxidants but close significant (P<0,01) on bacterial count had a very seriesof with the same water, protein, fat and antioxidant content but can reduce the number of bacteria, and the best treatment is using lemons (P3).